2008
DOI: 10.1021/jf072657a
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD-MS/MS-ESI Screening of Phenolic Compounds in Pieris brassicae L. Reared on Brassica rapa var.rapaL

Abstract: The phenolic profiles of cabbage white butterfly ( Pieris brassicae L.; Lepidoptera: Pieridae) at different development stages (larvae, exuviae, and butterfly), its excrements, and its host plant Brassica rapa var. rapa L. were determined by high performance liquid chromatography- diode-array detector-mass spectrometry/mass spectrometry-electrospray ionization (HPLC-DAD-MS/MS-ESI). Twenty-five acylated and nonacylated flavonoid glycosides and ferulic and sinapic acids were identified in host plant, from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
89
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 22 publications
13
89
0
Order By: Relevance
“…Flavonol sulfates also have been detected in the frass of larvae feeding on Caryodendron orinocense, P. guajava, S. reticulata, T. ochracea, T. bicolor, and V. braceliniae. Similar compounds were found earlier in the frass of lepidopteran Pieris brassicae (Ferreres et al 2008(Ferreres et al , 2009. Ruuhola et al (2001) found that generally over half of the flavonoids ingested by lepidopteran O. brumata could not be detected in larval frass, implying their efficient metabolism by the larvae.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Flavonol sulfates also have been detected in the frass of larvae feeding on Caryodendron orinocense, P. guajava, S. reticulata, T. ochracea, T. bicolor, and V. braceliniae. Similar compounds were found earlier in the frass of lepidopteran Pieris brassicae (Ferreres et al 2008(Ferreres et al , 2009. Ruuhola et al (2001) found that generally over half of the flavonoids ingested by lepidopteran O. brumata could not be detected in larval frass, implying their efficient metabolism by the larvae.…”
supporting
confidence: 72%
“…Some phenolic compounds are sequestered and reused by larvae, e.g., as wing pigments of adult butterflies (Burghardt et al 1997(Burghardt et al , 2001. Certain phenolic compounds proceed intact through the digestive tract of lepidopterans, while others are chemically modified by the larvae (Ferreres et al 2008;Ramos et al 2012;Salminen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon evaluating the MRM transitions corresponding to the 287xxx the results indicates (see Figure S5) that most likely more than 10 cyanidin containing compounds are present in the red onion sample. Peak nr 3,5,6,8,10,14,15,17,20,21,27,29,34,35, and 39 (see Figure S5), all show MRM patterns that are similar to the cyanidin standards that were analyzed in this study. The peak in Figure S5 with a retention time of 24.3 min (compound 10) has a retention time close to one of the available standards, Cy-3-rut entry 9 in Table 3, however, method 2 indicates that m/z 611 is the parent ion and not m/z 595.…”
Section: Plant Extractsmentioning
confidence: 53%
“…One approach found in the literature for achieving this utilizes basic and acidic hydrolysis in such a way that substituents are cleaved off, more or less completely, before chromatographic analysis. [8,[20][21][22] One limitation with this approach is that information about the number of flavonoids with a specific aglycone could not directly be obtained. Furthermore, C-linked substituents are more resistant against hydrolysis [8] , thus identity of those aglycones will not be obtained.…”
Section: Resultsmentioning
confidence: 99%